Integrals involving the homogeneous generalized hypergeometric function and multivariable Aleph-function - Frédéric, Ayant (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2022)
Link to publisher's homepage at https://amci.unimap.edu.my/